Assessment framework of building envelopes on energy efficiency for public buildings in Malaysia: the literature review / Izzat Anuar ... [et al.] - Anuar, Izzat; Abdul Karim, Norashikin; Hazim, Zulkarnain; Ahmad, Norfazillah (2022)
Measuring building envelopes with modern technologies is very important in determining the performance of energy efficiency. It has a significant impact on the environment, comfort for the users as well as energy consumption. Before heating, ventilating, and air-conditioning (HVAC) were introduced in Malaysia, building facades were created as part of passive design strategies for allowing natural ventilation and change in air pressures (stack effect) especially for public buildings. When HVAC was integrated into buildings, the building facades no longer provided these services. This paper aims to develop an assessment framework on the use of appropriate technology for environmentally efficient building envelopes in public buildings. Apart from that, this paper will research the passive design strategies in order to be applied to the public building envelopes that will solve the problems of providing protection against humidity and weather conditions. The approach of Design Quality Indicator (DQI) should be considered to address the quality of building envelope technology and external skin configuration, which includes functionality, build quality, and impact for evaluating qualitative improvements and adding value for the end-users. Highlights and summaries of the literature review will be made so that it can be used as a useful reference and source of advice for the construction business.